Eristalis (Eoseristalis) arbustorum - El-Hawagry, Magdi S.; Gilbert, Francis (Zenodo, 2019)
Eristalis ( Eoseristalis ) arbustorum (Linnaeus, 1758) Musca arbustorum Linnaeus, 1758: 591. Type locality: Sweden. Material examined : 1 female, St. Katherine, Sinai, 4.VII.2012, leg. Norfolk [unpublished thesis of Norfolk (2015)]. World distribution : NE: Wisconsin to Labrador, s. to Kansas & South Carolina. OR: India. PA: Algeria, Egypt, Europe (Fennoscandia southwards; from Ireland eastwards through much of Europe into Russia and on through Siberia to the Pacific coast (Sakhalin)), Morocco, Tunisia. Egyptian localities : Sinai: St. Catherine. Activity period in Egypt : July. Remarks : Norfolk (2015) found a female specimen of Eristalis arbustorum (L.) in St. Catherine, Sinai visiting Achillea fragrantissima . : Published as part of El-Hawagry, Magdi S. & Gilbert, Francis, 2019, Catalogue of the Syrphidae of Egypt (Diptera), pp. 201-248 in Zootaxa 4577 (2) on page 222, DOI: 10.11646/zootaxa.4577.2.1, http://zenodo.org/record/2629643 : {"references": ["Linnaeus, C. (1758) Systema Naturae per regna tria naturae, secundum classes, ordines, genera, species, cum characteribus, differentiis, synonymis, locis. Editio decima, reformata. Tomus I. Laurentii Salvii, Holmiae, 828 pp.", "Norfolk, O. (2015) Assessing the biodiversity impacts of Bedouin agricultural gardens. Unpublished PhD Thesis, University of Nottingham, Nottingham, 177 pp."]}